Hipersuperfacies Conformemente Planas no Espaço Euclidiano R4 - SOUSA, Marcio Lemes de (2008)
In this work we develop the article "Conformally Flat Hypersurfaces in Euclidean 4-space II", of Suyama, where is presented the study on conformally °at hypersurfaces in the Euclidean 4-spaces R4. From a surface with constant Gaussian curvature positive or negative in either Euclidean 3-space R3 or the standard 3-sphere S3, we constructed a family of conformally °at hypersurfaces in R4, with three distinct principal curvatures